Institutional culture and change : staff and pupils' perceptions. - Zitha, Phethile (My University, 2010)
As a country that has undergone socio-political changes in the recent past, South Africa is still developing in many respects. The education system has moved from a separate education policy for the different races to a multicultural education system. This research, therefore, proposes to investigate the extent to which these policy changes are implemented and responded to at schools, as well as the experiences and the perceptions of both teachers and pupils of racial integration at their school. The aim of this project to explore, recognize and at least attempt to understand the mechanisms and the processes that are present at schools as integrating institutions. Additionally this project aims to look at the relationship between the institutions’ culture and change as well as how both teachers and pupils experience and make sense of the school’s ethos and change (or lack thereof). Individual interviews were conducted with six pupils from grade 10 to grade 12, two participants from each grade, and with three staff members from Rose High School. Thematic content analysis was used to analyze the data to highlight and breakdown both manifest and hidden ideas or perceptions held by staff and the pupils around issues of institutional culture, and change at their school, which in turn helped in interpreting meaning from the data that was be collected. The findings show that despite some positive shifts, the lack of change in the language use, ‘academic culture’, assimilation instead of real integration and Black deprecation are reflective of the lack of change in the institutional culture of the school. These in turn inhibit transformation by maintaining the status quo, setting aside competence and privilege for White learners while lack of discipline and incompetence is left to African learners.